Assessment of Urinary Albumin-Creatinine Ratio and Estimated Glomerular Filtration Rate in Non-Diabetic Hypertensive Patients Attending a Tertiary Care Hospital in Chattogram, Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Hypertension is a major risk factor for Chronic Kidney Disease (CKD) often causing subclinical renal damage long before overt symptoms appear. Microalbuminuria, as reflected by the Urinary Albuminto-Creatinine  Ratio (UACR)  and a decline in estimated Glomerular Filtration Rate (eGFR) are key indicators of early renal impairment. Evaluating these parameters in non-diabetic hypertensive individuals can aid in timely identification of renal involvement. This study aimed to assess the UACR and eGFR in non-diabetic hypertensive patients compared to normotensive individuals attending a tertiary care hospital in Chattogram, Bangladesh.Materials and methods: This hospital-based crosssectional  comparative study was conducted at Chittagong Medical College Hospital during the period from January to December 2023. A total of 136 participants were enrolled using purposive sampling and divided into two equal groups: hypertensive (n=68) and normotensive (n=68). Key variables were measured include UACR, eGFR, systolic and diastolic blood pressures, Body Mass Index (BMI) serum creatinine and lipid profile.Results: The prevalence of microalbuminuria was significantly higher in the hypertensive group compared to the normotensive group (33.8% vs. 7.4%, p